Estimation of carbon storage and influencing factors for urban green spaces: a view of green space types and plant community structure - Wang, Xiaoge; Xue, Wei; Ruan, Yu; Cheng, Mengyao; Ma, Shuying (Frontiers in Environmental Science, 2026)
Urban green space (GS) is a major spatial carrier for carrying out carbon sequestration (CS) function. The CS capacity of GS is affected by different resource circumstances, climatic traits, and urban management policies. By examining the variations in carbon storage and the affecting variables across many kinds of GSs and suggesting optimization plans, urban planners may scientifically boost the CS of GS. Focusing on the Xi’an urban region, in this paper, we estimate and examine the carbon storage and spatial distribution features of various kinds of GSs in the Xi’an urban area using field survey and remote-sensing technology. The findings reveal notable changes in the carbon storage capacity of multiple kinds of GSs as well as varying influences of their landscape design elements on carbon storage. By choosing representative plant communities in Xi’an World Expo Park, in this paper, we investigate the link between CS effect and plant community structure. The findings of the study indicate that the tree diameter at breast height and plant community density positively correlate with the carbon storage per unit area; regression analysis reveals the pattern of curve changes in plant community CS impact. A sustainable CS point of view optimization plan for urban GS CS has been suggested based on the above findings.